2020
DOI: 10.3390/atmos11121366
|View full text |Cite
|
Sign up to set email alerts
|

Pollution Caused by Potentially Toxic Elements Present in Road Dust from Industrial Areas in Korea

Abstract: We examined the pollution characteristics of potentially toxic elements (PTEs) in road dust (RD) from nine industrial areas in South Korea to assess PTE pollution levels and their environmental risks for devising better strategies for managing RD. The median concentrations (mg/kg) were in the order Zn (1407) > Cr (380) > Cu (276) > Pb (260) > Ni (112) > As (15) > Cd (2) > Hg (0.1). The concentration of PTEs was the highest at the Onsan Industrial Complex, where many smelting facilities are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…From 2010 to 2014, the average PM10 level in the ambient air near the investigated ICs was 42-52 μg/m 3 per year, exceeding the annual PM10 permissible level set by the world health organization (20 μg/m 3 ) [73]. The number of employees in the ICs investigated in this study ranges from approximately 8,000 to 300,000, and there will likely be many road users in these areas [44]. Moreover, the ICs are based an average of 14.25 km away from residential areas with infrastructure, and 45% are located within 10 km from residential areas [69].…”
Section: Study Areasmentioning
confidence: 76%
See 4 more Smart Citations
“…From 2010 to 2014, the average PM10 level in the ambient air near the investigated ICs was 42-52 μg/m 3 per year, exceeding the annual PM10 permissible level set by the world health organization (20 μg/m 3 ) [73]. The number of employees in the ICs investigated in this study ranges from approximately 8,000 to 300,000, and there will likely be many road users in these areas [44]. Moreover, the ICs are based an average of 14.25 km away from residential areas with infrastructure, and 45% are located within 10 km from residential areas [69].…”
Section: Study Areasmentioning
confidence: 76%
“…Map and sampling stations of nine industrial complexes where RDS was collected in this study. PM10 samples from in this study were separated from bulk RDS samples of our previous study [44]. More detailed information of the study area can be obtained from the previously reported study [44].…”
Section: Study Areasmentioning
confidence: 99%
See 3 more Smart Citations